Impact of Internet Use on Social Media on the Learning Process: Focus on Early Childhood - Miranti; Letisa; Muhtasyim Adib (International Journal of Education and Teaching Zone)
This research aims to determine the impact of using the internet on social media on the learning process that focuses on early childhood. In this research, researchers used quantitative descriptive research methods. We specialize in this research to review or examine the general use of social media in early childhood, both its impact and existence at school. This research was conducted at Permata Ibu Kindergarten with a population of 18 students, nine boys, and nine girls, with a sample size of 18 students and one teacher using total sampling techniques. The instrument used was a questionnaire consisting of 15 questions. The research found that the internet in schools is still very low due to reasonably good management and school rules and also the role of parents who are very good and selective, where social media use is in the low category at 89%. In comparison, the medium category is 11%.